THE SCALE AND PREVALENCE OF INCLUSIVE EDUCATION FOR MINORS IN MOSCOW: THE POSSIBILITIES FOR QUANTITATIVE ASSESSMENT - Oksana V. Kuchmayeva; Olga L. Petrjakova (Статистика и экономика)
The article is devoted to the problems of assessingthe prevalence of inclusive education. The authors on the issues of statistical accounting of such category of students as children with disabilities, aswell as the educational institutions providing educational services, are assessing the needs in inclusiveeducation. During the analysis the authors usedthe data of statistical accounting, materials of thesample study «Availability of educational services for children with disabilities in the Moscow».